Interferensi Linguistik dalam Gaya Bahasa Masyarakat Pengguna Media Sosial Instagram Akun Cinta Laura Kiehl - Candra Oftriyana; Ropita Ropita; Syahrul Ramadhan; Elfia Sukma; Norliza Jamaluddin (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study discusses the phenomenon of language interference on the Instagram account of public figure Cinta Laura Kiehl. Language interference is a language phenomenon characterized by the entry of elements from one language into another language commonly used by bilingual or multilingual speakers. In this context, the interference of Indonesian and English on Cinta Laura's Instagram account is interesting to study because of its consistent and striking use in various uploads and digital interactions. This study uses a qualitative descriptive approach with a content analysis method on data in the form of image captions uploaded by Cinta Laura at a certain time. The results of the study show that the interference that appears can be classified into several linguistic levels, namely lexical, morphological, syntactic, and semantic levels. Lexical interference appears in the use of English vocabulary in Indonesian sentences. Meanwhile, morphological interference is seen from the structure of mixed word formation that does not comply with the rules in Indonesian. Syntactic interference appears in the form of sentence structures that follow the structure of English. Factors that cause interference include the speaker's bilingual background, the habit of using foreign languages ​​in everyday life, the influence of an international social environment, and expressive and modern communication styles on social media. This study shows that interference in the context of social media is not merely a form of language deviation, but can also be seen as part of the construction of self-identity and digital communication strategies. These findings are expected to contribute to contemporary sociolinguistic studies and enrich understanding of the dynamics of language use in digital public spaces.